PARASITIC INFECTIONS OF THE COMMON CARP Cyprinus carpio FROM LESSER ZAB RIVER IN KURDISTAN REGION, IRAQ - Mama, Kamaran S.; Abdullah, Shamall M. A. (European Scientific Journal, ESJ, 2014)
A total of 150 common carp Cyprinus carpio were collected from Lesser Zab river, near Alton Kupri, south of Erbil city, Kurdistan region, Iraq, during the period from August 2010 until the end of May 2011. The fishes were examined for ecto- and endoparasites. The study revealed the existence of nine species of parasites. These included two species of protozoans (Ichthyophthirius multifiliis and Trichodina reticulata), four species of monogeneans (Gyrodactylus baikalensis, G. elegans, G. gobioninum and G. vicinus), one species of each of trematode (Diplostomum spathaceum), cestode (Bothriocephalus acheilognathi) and crustacean (Lernaea cyprinacea). The record of G. gobioninum in the present study is considered as the first record in Iraq, and T. reticulata and G. baikalensis in Kurdistan region. Also, C. carpio is regarded as a new host for T. reticulata in Iraq.